Sintesis dan Karakterisasi Nanopartikel CuO-Kitosan serta Uji Antibakteri terhadap Streptococcus pneumoniae - Qomariyah, Ani; Wulandari, Eka Yunita; Najib, Ainun (Chemistry Department, Universitas Islam Indonesia, 2025)
The green chemistry technique was carried out for the first time to synthesize CuO-Chitosan nanoparticles using CuSO4 as a precursor and red dragon fruit peel extract as a reducing agent which was then applied as an antibacterial agent. The extraction procedure of red dragon fruit peel was carried out by maceration technique with methanol solvent. CuO-chitosan nanoparticles were produced through green chemistry with reduction method. The compounds in the red dragon fruit peel extract reduced Cu2+ to Cu. The successfully synthesized Cu-NPs were analyzed using FT-IR, SEM, PSA, and UV-Visible Spectrophotometer. The variation of reducing agent volume affected the maximum wavelength produced. The optimum reducing agent concentration (1:5) showed the highest intensity at 650 nm. The optimum pH for CuO-Chitosan synthesis was 6. Cu-NPs were stable at 20 minutes to 1 hour. Identification of functional groups with FTIR showed a shift in wave numbers between pure CuSO4 precursor and CuO-Citosan Nanoparticles, indicating the interaction of functional groups. Volume or weight analysis of CuO-Citosan Nanoparticles using PSA gave particle diameters between 80 and 120 nm with an approximate distribution of 100 nm. The results of the antibacterial test showed that the growth of Streptococcus pneumoniae bacteria produced the highest inhibition zone in CuO-Citosan Nanoparticles with a concentration of 100% which had an average inhibition zone diameter of 11 mm. This proves that CuO-chitosan nanoparticles are effective against Streptococcus pneumoniae. Keywords: CuO-chitosan, nanoparticles, Streptococcus pneumoniae